EFEKTIVITAS ANTIBAKTERI Nigella sativa TERHADAP Methicillin-Resistant Staphylococcus aureus: SYSTEMATIC REVIEW - Namira Salma Ghinanafsi, (2022)
Antimicrobial resistance is reported as one of ten global health threats. The average prevalence of Methicillin-resistant Staphylococcus aureus infection in Indonesia reached 38% and if a solution is not found immediately, it is estimated that in 2050 there will be ten million deaths in the world because of antibiotic resistance. One of the promising traditional remedies from natural resources that has been used for a long time is black cumin. The purpose of this study was to determine the antibacterial activity of black cumin extract against MRSA. A systematic review was carried out with PRISMA-P 2020 strategy using PICO method from Google Scholar, PubMed, and ProQuest databases in the last ten years. The eight research articles that met the inclusion criteria were assessed for literature quality and risk of bias using the JBI quasi experimental. The methods used are microdilution, well diffusion, disc diffusion, and agar dilution with Mueller-Hinton incubated for 24 hours. Analysis showed that the antibacterial activity of black cumin extract was strong in two literatures and very strong in three literatures with a maximum inhibition zone range of 25-86 mm, while three out of four literatures showed MRSA susceptibility to black cumin with the smallest MIC <0.25 g/mL. These results are due to the presence of bioactive compounds in black cumin, such as thymoquinone, thymohydroquinone, thymol, p-cymene, and tannins that has ability to inhibit biofilm formation and adhesion, inactivation of enzymes and efflux pumps, reduce membrane integrity, and suppress oxidative activity.